Eating Behavior and Obesity in Canada - Sunday Azagba PhD candidate; Mesbah F. Sharaf PhD candidate (SAGE Publishing, 2012)
Background : Although a growing body of research has examined the association between food prices and the availability of fast food restaurants on weight outcomes, there is limited empirical evidence on the direct effect of eating behavior on body weight. Objective : The effect of eating behavior on obesity prevalence among Canadians is examined. Methods : A nationally representative sample from the Canadian National Population Health Survey (2000-2008) with 29 722 observations is used. Obesity prevalence is estimated by a linear probability model using cross-sectional and panel estimation methods. Separate regressions are estimated for males and females. Results : Multivariate analyses suggest that eating behavior has a statistically significant effect on obesity prevalence. In particular, individuals who reported excellent, very good, and good eating behavior have a lower risk of obesity compared with those with fair or poor eating behavior. Although cross-sectional and panel data methods produce consistent results, the cross-sectional model overestimates the effect of eating behavior on the risk of obesity. This highlights the importance of controlling for unobserved individual factors that may affect how eating behavior is related to body weight. Conclusion : Evidence is found showing that eating behavior is an important determinant of obesity prevalence. The findings suggest that improving the eating behavior of individuals would help reduce excessive body weight and its induced health risks.